ANCAMAN PIDANA DALAM PEMUTAKHIRAN DATA PEMILIH BERKELANJUTAN TERHADAP PEMILIH LUAR NEGERI DI KABUPATEN BADUNG - Ni Komang Puspita Dewi; Anak Agung Gede Ananta Wijaya Sahadewa; Agung Rio Sandiswara (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Article 544 concerning data falsification, and KPU Regulation Number 1 of 2025, emphasizes verification through the Annual Coklit System (Coktas), synchronization with Dukcapil, and digital trail audits to guarantee the legality of the identity and existence of overseas voters such as the management of 2,417 PDPB data for Quarter IV 2025 by the Badung KPU. The theory of legal certainty reveals normative voids (vacuum normarum) and vague norms (norma in determinata) in these regulations, such as the absence of systematic cross-border verification, which causes reliance on administrative data alone and the risk of marginalizing the constitutional rights of diaspora as subjects of dignified political rights. Challenges for the Badung KPU include the absence of ad hoc bodies such as the PPK and PPS in the non-stage period, high mobility of diaspora voters, and suboptimal cross-agency coordination, which threatens the validity and accountability of the DPT. The humanist approach via this theory highlights the urgency of restorative innovations that respect human dignity, such as real-time integration with the Ministry of Foreign Affairs, to realize inclusive democracy and protect political rights as the essence of people's sovereignty. This empirical research concludes that strengthening repressive-preventive legal certainty is imperative to prevent administrative fraud, while maintaining the essence of political rights as inherent, irreplaceable human rights for all citizens.